2021
DOI: 10.1097/gme.0000000000001713
|View full text |Cite
|
Sign up to set email alerts
|

#Menopause on Instagram: a mixed-methods study

Abstract: Objective: The aims of this study were to: (1) characterize the menopause transition (MT) on social media and (2) determine if concordance or discordance exists when comparing MT-focused social media posts and biomedical research literature. Methods: We analyzed 440 sequential Instagram posts with the hashtag #menopause over 2 weeks from January to February 2019. Posts were composed of 299 unique accounts, resulting in an average of 1.7 posts per accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Instead, women turn to social media for social support, e.g. Facebook (Cronin, 2017), or Instagram (Arseneau et al, 2021), however, the quality of the information exchanged in these forums is variable, often based on misinformation. Søgaard Neilsen and Wilson (2019) work suggests a strong uptake of digital technologies in midlife women.…”
Section: )mentioning
confidence: 99%
“…Instead, women turn to social media for social support, e.g. Facebook (Cronin, 2017), or Instagram (Arseneau et al, 2021), however, the quality of the information exchanged in these forums is variable, often based on misinformation. Søgaard Neilsen and Wilson (2019) work suggests a strong uptake of digital technologies in midlife women.…”
Section: )mentioning
confidence: 99%
“…For example, individuals turn to YouTube for information on gynecologic and sexual health [5], and to Reddit for information regarding sexually transmitted infection (STI) diagnoses [6]. Content posted on social media serves as a source of information for clinicians and patients to better understand peoples' experiences with miscarriage [7], menopause [8], lupus and pregnancy decision making [9], and emergency contraception [10]. Importantly, social media influences health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attention has turned to social media and the menopause. For example, a study of posts on the social media platform Instagram [1] found images, video and/or text about menopause that included advertisements (48%), advice on self-care (47%), and physical health (44%).…”
Section: Introductionmentioning
confidence: 99%